Search for lepton flavour violation in the e[mu] continuum with the ATLAS detector in √s=7 TeV pp collisions at the LHC - Aad, Georges; Anders, Christoph; Andrei, George Victor; Childers, J. Taylor; Dietzsch, Thorsten; Geweniger, Christoph; Hanke, Paul; Henke, Michael; Khomich, Andrei; Kluge, Eike-Erik; Kugel, Andreas; Lendermann, Victor; et al. (The European physical journal. C, Particles and fields, 2012)
This paper presents a search for the t-channel exchange of an R-parity violating scalar top quark (t~t~\tilde{t}) in the e ± μ ∓ continuum using 2.1 fb−1 of data collected by the ATLAS detector in s√=7 TeVs=7 TeV\sqrt{s}=7~TeV pp collisions at the Large Hadron Collider. Data are found to be consistent with the expectation from the Standard Model backgrounds. Limits on R-parity-violating couplings at 95 % C.L. are calculated as a function of the scalar top mass (mt~mt~m_{\tilde{t}}). The upper limits on the production cross section for pp→eμX, through the t-channel exchange of a scalar top quark, ranges from 170 fb for mt~=95 GeVmt~=95 GeVm_{\tilde{t}}=95~GeV to 30 fb for mt~=1000 GeVmt~=1000 GeVm_{\tilde{t}}=1000~GeV.